Effect of Y on the Microstructures and Heat-Resistant Property of ZL109 Alloys - Xiangdu Qin; Anmin Li; Xiang Li (Crystals)
The effects of rare earth Y on the microstructures and tensile properties of ZL109 alloys were studied through metallographic observation, scanning electron microanalysis, X-ray diffraction, and tensile experiments, and the existence form and mechanism of Y were analyzed. The results show that the grain size of the ZL109 alloy is obviously reduced and that the strength of the ZL109 alloy is significantly increased after adding the Y element. When the Y content is increased to 0.2 wt.%, the tensile properties of the ZL109 alloy at room temperature and 350 °C are better than those without a rare earth addition, and the comprehensive tensile properties are better. This is due to the addition of the Y element; α-Al dendrites are obviously refined, and there is a tendency for them to change into fine isometric crystals. The size of the eutectic Si decreases, and its shape is modified. The morphology and size of high temperature enhanced phases, such as Al3CuNi, are optimized. The heat-resistant enhanced phase Al2Si2Y is formed after the addition of rare earth Y. However, with the addition of the Y element, the Al2Si2Y phase increases, and coarsening results in the decrease in alloy strength.